Longitudinal Study of Total and Pathogenic Vibrio parahaemolyticus (tdh+ and/or trh+) in Two Natural Extraction Areas of Mytilus chilensis in Southern Chile - Bacian, Cristina; Verdugo, Cristobal; García, Katherine; Perez-Larruscain, Josu; de Blas, Ignacio; Cachicas, Viviana; Lopez-Joven, Carmen (Frontiers in Microbiology, 2021)
Vibrio parahaemolyticus is the leading cause of seafood-associated bacterial gastroenteritis worldwide. Although different studies have focused on its pattern of variation over time, knowledge about the environmental factors driving the dynamics of this pathogen under the Chilean territory is still lacking.. This study determined the prevalence of total and pathogenic V. parahaemolyticus strains (tdh and/or trh genes) in mussels (Mytilus chilensis) collected from two natural growing areas between 2017 and 2018, using selective agar and PCR analysis. V. parahaemolyticus was detected in 45.6 % (93/204) of pooled samples from Valdivia River Estuary. The pathogenic strains carrying tdh and/or trh gene were detected in 11.8 % (24/204): tdh in 9.8 % (20/204), trh in 0.5 % (1/204), and 1.5 % (3/204) presented both genes. In Reloncaví Fjord, V. parahaemolyticus was detected in 14.4 % (30/209) of samples, pathogenic V. parahaemolyticus carrying trh gene was detected in 0.5 % (1/209) of samples, while tdh gene was not detected in samples from this area. The total count of mauve-purple colonies typical of V. parahaemolyticus on CHROMagar was positively associated by multivariate analysis with area, water temperature and salinity. Similarly, V. parahaemolyticus detection rates by PCR had positive correlation with area and water temperature. The chances of detecting total V. parahaemolyticus in Valdivia River Estuary are significantly higher than Reloncaví Fjord, but inversely, during spring-summer months, the interaction factor between area and time, indicated that the chances of detecting V. parahaemolyticus are higher in Reloncaví Fjord. Interestingly, this period coincides with the season when commercial and natural-growing shellfish are harvested. On the other hand, pathogenic V. parahaemolyticus tdh+ was significantly correlated with an increase of water temperature. These environmental parameters could be used to trigger a warning on potential hazard, which would influence human health and economic losses in aquaculture systems.